PERSEPSI PETANI KENTANG TERHADAP KEMITRAAN DI KECAMATAN PANGALENGAN, KABUPATEN BANDUNG - Anisa Salsabila; Eliana Wulandari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The agricultural sector is a sector that can be a supporting and supporting sector in the development of other sectors. The potato commodity is directed as one of the commercial commodities in the context of exploiting market opportunities. Partnerships can assist farmers in overcoming problems faced by farmers such as access to capital, technology and markets. The existing partnership in Pangalengan District is PT. Indofood Frytolay Makmur, supermarket supplier, and TaniHub.This study aims to analyze the perception of potato farmers in Pangalengan District, Bandung Regency on partnerships, especially in Pulosari and Pangalengan villages. Sampling in this study using a proportionate stratified random sampling technique of 52 respondents. The design used in this research is a quantitative design using a survey method. Data analysis using descriptive method. The results showed that the farmers' perceptions of the majority partnership were in the good category.